The Concept of Corporate Criminal Liability in the Law on Information and Electronic Transactions - Hartoto Suci Rahayu; Diana Lukitasari (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
The development of cyber crime gives birth to new facts that corporations can become perpetrators of criminal acts, therefore it is necessary to impose criminal responsibility on the corporation. The purpose of this research is to find out the criminal responsibility of corporations in Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions. The type of research in writing this journal is normative or doctrinal by using a statutory approach and taking primary and secondary legal materials. Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions adopts the doctrine of identification in imposing criminal liability on corporations. In addition, actions against the law by the management and / or staff of the corporation can be subject to criminal liability based on the doctrine of vicarious liability.